Improving Operational Performance through Competitiveness and Implementation Management Quality Integrated - Ramlawati, Ramlawati; Imaduddin, Imaduddin; Alisyah, Nur; Nirina, Nurul (Journal La Bisecoman, 2024)
The challenge in implementing quality management effectively in MSMEs lies in the tight market competition and the dynamics of the ever-changing industrial environment. Although MSMEs have great potential to improve the economy and absorb labor, various obstacles such as low product quality, limited human resources and technology still hamper development. This study aims to determine and analyze the effect of the implementation of Total Quality Management on the quality competitiveness and improvement of operational performance of MSMEs in Makassar City. Data were analyzed using descriptive statistical techniques and Structural Equation Modeling (SEM), with validity testing through normality and reliability tests. The results of the study indicate that the implementation of Total Quality Management (TQM) has a positive and significant effect on the quality competitiveness of MSMEs in Makassar City. TQM improves product quality, makes MSMEs more competitive in the market, and helps manage the production process more efficiently, reduces errors, and increases customer satisfaction. Although TQM also has a positive impact on operational performance, its effect is not significant, indicating that other elements such as human resources, technology, and the business environment also influence. Overall, TQM contributes to improving operational performance through quality competitiveness and operational efficiency. The output produced from this study is in the form of scientific publications. Theoretically, it becomes a theoretical basis for quality management practices, quality competitiveness and improving operational performance in Micro, Small and Medium Enterprises in Makassar City.